MODELO MATEMÁTICO PARA LA TRANSFRUCTOSILACIÓN DE ESTEVIÓSIDO CON - FRUCTOFURANOSIDASA INMOVILIZADA - Cárdenas T., Fiorella (2019)
In the present article, a mathematical model for the b- immobilized fructofuranosidase was constructed considering the partition equilibrium between the liquid phase and the particle, diffusion and reaction within the particle. The kinetic constants were estimated by fitting the kinetic equations with the experimental data of the fructosyl-stevioside experiments using suspended enzyme. The other constants were estimated by fitting the mathematical model with experimental data of partition equilibrium coefficient, and fructosyl-stevioside synthesis using immobilized enzyme. The model could describe the fructosyl-stevioside formation under several conditions of initial concentration of substrate and total enzyme in the system.